Microbial Fuel Cell Based Thermosensor for Robotic Applications - Greenman, John; Mendis, Arjuna; You, Jiseon; Gajda, Iwona; Horsfield, Ian; Ieropoulos, Ioannis (Frontiers in Robotics and AI, 2021)
On the road-map to building a completely autonomous robot, all aspects of the robot: energy generation, processing, sensing and actuation, need to be self-sustainable and perhaps function in the biological realm. Microbial Fuel Cells (MFC) provide a platform technology for achieving this goal. In a series of experimental steps, we demonstrate that MFCs can be used as living, autonomous sensors in robotics. In this work, we focus on thermal sensing that is akin to thermoreceptors in mammalian entities. The thermosensor was able to detect stimuli of 1 min directed from a distance of 10 cm causing a temperature rise of ~1°C at the sensor. Continuous stimuli were detected at a minimal interval of 384 s. For demonstration of practical application; a mobile robot was fitted two artificial thermosensors for thermotaxis application, enabling the robot to detect thermal stimulus and steer away from a warmer thermal source within the rise of 1°C. Continuous thermal stimuli were detected at a minimal time interval of 160 s